Smoke on the mountain : an interpretation of the Ten Commandments - Davidman, Joy, 1915-1960 (Westminster Press, 1985)
This celebrated book, a dynamic and original interpretation of the Ten Commandments, is enhanced by a thoughtful introduction by C. S. Lewis, the author's husband. Lewis writes, "the flaw in us which Joy Davidman seems to me to expose with most certainty will be to some perhaps an unexpected one: the sin of fear . . . quite simply, cowardice."